Gender Differences in Temperament A Meta-Analysis. [article]. - Else-Quest, Nicole M.
The authors used meta-analytical techniques to estimate the magnitude of gender differences in mean level and variability of 35 factors of temperament in children ages e months to 13 years. Effortful control showed a large difference favoring girls and the dimensions within that factor (e. g., inhibitory control: d = 0.41, perceptual sensitivity: d = 0.38) showed moderate gender differences favoring girls, consistent with boys' greater incidence of externalizing disorders. Surgency showed a difference favoring boys, as did some of the dimensions within that factor(e. g., activity d = 0.33, high-intensity pleasure: d = 0.30), consistent with boys' greater involvement in active rough-and-tumble play. Negative affectivity showed negligible gender differences. -- (from the author)